2016
DOI: 10.1080/2162402x.2016.1258505
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 and oxidative stress underlie the immunogenic potential of high hydrostatic pressure-induced cancer cell death

Abstract: High hydrostatic pressure (HHP) promotes key characteristics of immunogenic cell death (ICD), in thus far resembling immunogenic chemotherapy and ionizing irradiation. Here, we demonstrate that cancer cells succumbing to HHP induce CD4 C and CD8 C T cell-dependent protective immunity in vivo. Moreover, we show that cell death induction by HHP relies on the overproduction of reactive oxygen species (ROS), causing rapid establishment of the integrated stress response, eIF2a phosphorylation by PERK, and sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…71 Of note, the ICDassociated exposure of some ER chaperones (notably, CALR) on the cell surface appears to be regulated by C-X-C motif chemokine ligand 8 (CXCL8), 184 ER Ca 2+ levels, 185 as well as CASP2, long non-coding RNAs (eg, ncRNA-RB1 and miR-27a), and plasma membrane integrins, at least in some settings. [186][187][188][189] Surface-exposed CALR (and other ER chaperons) promotes the uptake of dying cells or their corpses by APCs, at least in some settings on interaction with LDL receptor related protein 1 (LRP1). 178 190 Moreover, CALR exposure appears to drive type I IFN secretion by APCs, 191 192 which is also expected to contribute to the immunogenicity of RCD.…”
Section: Sources Of Icd Antigenicitymentioning
confidence: 99%
“…71 Of note, the ICDassociated exposure of some ER chaperones (notably, CALR) on the cell surface appears to be regulated by C-X-C motif chemokine ligand 8 (CXCL8), 184 ER Ca 2+ levels, 185 as well as CASP2, long non-coding RNAs (eg, ncRNA-RB1 and miR-27a), and plasma membrane integrins, at least in some settings. [186][187][188][189] Surface-exposed CALR (and other ER chaperons) promotes the uptake of dying cells or their corpses by APCs, at least in some settings on interaction with LDL receptor related protein 1 (LRP1). 178 190 Moreover, CALR exposure appears to drive type I IFN secretion by APCs, 191 192 which is also expected to contribute to the immunogenicity of RCD.…”
Section: Sources Of Icd Antigenicitymentioning
confidence: 99%
“…Specifically, eIF2αP in tumors has been linked to the induction of immunogenic cell death (ICD) 55 , which requires the activation of immune-mediated anti-tumor responses in the tumor bed in response to certain chemotherapeutic drugs 56 . A recent study showed that increased ROS in TSC-proficient tumor cells under hydrostatic pressure activates the PERK-eIF2αP arm and promotes ICD 57 . Thus, the effects of PERK and eIF2αP on tumor formation under pro-oxidant conditions may engage both cell-autonomous and immune-regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the UPR‐dependent mechanism is crucial for ecto‐CRT induction through concerted action of two major interconnected signaling‐arms i.e. the PKR‐like ER kinase (PERK)‐based phosphorylation of eIF2α (one of the UPR arms wherein PERK is a key ER stress sensor) and a caspase signaling axes (consisting of caspase‐8, caspase‐2, BAP31 and BAX/BAK, in an ICD‐inducer‐dependent fashion) . On the other hand, the UPR‐independent mechanism is crucial for both ecto‐CRT induction and ATP secretion, and is largely executed via PERK‐based regulation of the secretory pathway .…”
Section: Tolerogenic Inflammatory and Immunogenic Cell Death Duringmentioning
confidence: 99%
“…and BAX/BAK, in an ICD-inducer-dependent fashion). 150,159 On the other hand, the UPR-independent mechanism is crucial for both ecto-CRT induction and ATP secretion, and is largely executed via PERKbased regulation of the secretory pathway. 73 In general, ER-to-Golgi transfer, Ca 2+ -modulated secretory pathway and actin cytoskeleton are crucial for both these trafficking mechanisms (see Table 2).…”
Section: Immunogenic Cell Death (Icd) In Cancermentioning
confidence: 99%